Solvothermal Synthesis of Acmite Conversion Coatings on Steel. Issue 11 (1st October 2013) - Whalen, Terence; VanSaders, Bryan; Vakifahmetoglu, Cekdar; Mughal, Asad; Zlotnikov, Eugene; Cho, Seung‐Beom; Riman, Richard E.
Abstract : Acmite (NaFeSi2 O6 ) films were formed on steel coupons via solvothermal reaction of silica, sodium hydroxide, and 1, 4‐butanediol in an autoclave under autogenous pressure. Systematic variation in processing variables led to homogenous coatings comprised of pinacoidal acmite grains with an average grain size of 33 μm. The coatings were produced on the steel coupons from reactant conditions of 0.635 m SiO2, 2.546 m NaOH, and 3.087 m 1, 4‐butanediol for 72 h at 240°C.